Perilaku Bullying dan Upaya Guru BK dalam Mengatasinya - Richo Surya Pradana; Firlia Candra Kartika; Ratih Agustin Rachmaningrum (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The school environment is often the target and spotlight of bullying behavior. The role of education in overcoming bullying behavior is associated with the efforts of guidance and counseling teachers at school. Guidance and counseling teachers can provide counseling services individually or in groups, with the aim of understanding the conditions and situations that are happening to students at school. This can make it easier to overcome, prevent and provide solutions to every problem that occurs to students. The research method used is a qualitative research method with data collection techniques of observation, interviews and documentation. This research is descriptive research with the aim of describing the forms of bullying behavior that occur at SMPN XY Malang City, as well as the efforts of guidance and counseling teachers in dealing with this problem. The subjects in this research were 8th grade students at SMPN XY Malang City. The results of this research show that the type of bullying behavior that often occurs is verbal harm which can ultimately cause mental harm. The guidance and counseling teacher at SMPN XY Malang created a social media account according to developments in the millennial generation. The results of the videos and posters presented by the BK teacher are aimed at providing education to students regarding the services provided.